The protective effect of CXC chemokine receptor 2 antagonist on experimental bronchopulmonary dysplasia induced by postnatal systemic inflammation - Seung Hyun Lee; Chang Won Choi (The Korean Pediatric Society, 2021)
Background Animal studies have shown that a leukocyte influx precedes the development of bronchopulmonary dysplasia (BPD) in premature sheep. The CXC chemokine receptor 2 (CXCR2) pathway has been implicated in the pathogenesis of BPD because of the predominance of CXCR2 ligands in tracheal aspirates of preterm infants who later developed BPD. Purpose To test the effect of CXCR2 antagonist on postnatal systemic and pulmonary inflammation and alveolarization in a newborn Sprague-Dawley rat model of BPD. Methods Lipopolysaccharide (LPS) was injected intraperitoneally (i.p.) into the newborn rats on postnatal day 1 (P1), P3, and P5 to induce systemic inflammation and inhibit alveolarization. In the same time with LPS administration, CXCR2 antagonist (SB-265610) or vehicle was injected i.p. to investigate whether CXCR2 antagonist can alleviate the detrimental effect of LPS on alveolarization by attenuating inflammation. On P7 and P14, bronchoalveolar lavage fluid (BALF) and peripheral blood (PB) were collected from the pups. To assess alveolarization, mean cord length and alveolar surface area were measured on 4 random nonoverlapping fields per animal in 2 distal lung sections at ×100 magnification. Results Early postnatal LPS administration significantly increased neutrophil counts in BALF and PB and inhibited alveolarization, which was indicated by a greater mean cord length and lesser alveolar surface area. CXCR2 antagonist significantly attenuated the increase of neutrophil counts in BALF and PB and restored alveolarization as indicated by a decreased mean cord length and increased alveolar surface area in rat pups exposed to early postnatal systemic LPS. Conclusion CXCR2 antagonist preserved alveolarization by alleviating pulmonary and systemic inflammation induced by early postnatal systemic LPS administration. These results suggest that CXCR2 antagonist can be considered a potential therapeutic agent for BPD that results from disrupted alveolarization induced by inflammation.